Financial dollarization and currency substitution: an empirical study for Bolivia - Salvatore Dell'Erba; Martin Saldías Zambrana (Kiel Institute for the World Economy (IfW), 2006)
The Bolivian puzzle is high and persistent financial dollarization notwithstanding deep macroeconomic stabilization that achieved stable and low inflation and the regulations encouraging domestic currency deposits. We analyze traditional and new approaches to explain dollarization in Bolivia. We first assess the currency substitution approach and then assess the empirical evidence for the financial dollarization approach. The results show that the macroeconomic variables capture only partially the phenomenon and a better assessment relies on other explanations such as the peso problem and the analysis of specific characteristics of the financial markets in Bolivia.
Keywords: E44; E59; G19; 330; Dollarization; Exchange rate regimes; Inflation; Bolivia